Primary Hyperoxaluria Type 1: The First Patient Treated with Lumasiran in Portugal - Borges,Madalena Almeida (2023)
ABSTRACT Primary hyperoxaluria type 1 is a rare genetic disease caused by mutations in AGXT, leading to an excessive hepatic production of oxalate, resulting in urolithiasis, nephrocalcinosis and chronic kidney disease. The authors present the case of a young female with PH1 who is the first patient treated with lumasiran in Portugal, and currently has a follow-up of 18 months.